2021
DOI: 10.1038/s41418-021-00752-9
|View full text |Cite|
|
Sign up to set email alerts
|

OTUB1 prevents lethal hepatocyte necroptosis through stabilization of c-IAP1 during murine liver inflammation

Abstract: In bacterial and sterile inflammation of the liver, hepatocyte apoptosis is, in contrast to necroptosis, a common feature. The molecular mechanisms preventing hepatocyte necroptosis and the potential consequences of hepatocyte necroptosis are largely unknown. Apoptosis and necroptosis are critically regulated by the ubiquitination of signaling molecules but especially the regulatory function of deubiquitinating enzymes (DUBs) is imperfectly defined. Here, we addressed the role of the DUB OTU domain aldehyde bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…In their absence TWEAK signaling and gene expression are greatly diminished [52]. OTUB1 works by inhibiting cytokine gene transcription within the immune system and regulates c-IAP1 via K48-linked polyubiquitination [53]. When OTUB1 is downregulated, it leads to much faster degradation of c-IAP1 and as a consequence, weaker TWEAK signaling [52,53].…”
Section: Regulation Of Tweak Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their absence TWEAK signaling and gene expression are greatly diminished [52]. OTUB1 works by inhibiting cytokine gene transcription within the immune system and regulates c-IAP1 via K48-linked polyubiquitination [53]. When OTUB1 is downregulated, it leads to much faster degradation of c-IAP1 and as a consequence, weaker TWEAK signaling [52,53].…”
Section: Regulation Of Tweak Expression and Functionmentioning
confidence: 99%
“…OTUB1 works by inhibiting cytokine gene transcription within the immune system and regulates c-IAP1 via K48-linked polyubiquitination [53]. When OTUB1 is downregulated, it leads to much faster degradation of c-IAP1 and as a consequence, weaker TWEAK signaling [52,53]. Interestingly, only canonical NF-κB and MAPK signaling are affected by the downregulation of OTUB1, which temporarily (as the non-canonical pathway is still functional) lowers the volume of produced cytokines including TNFα [32,52].…”
Section: Regulation Of Tweak Expression and Functionmentioning
confidence: 99%
“…We found that hepatocytes isolated from old mice exhibit increased necroptosis relative to hepatocytes from young mice, suggesting that necroptotic hepatocytes might be a major source of DAMPs in aging liver. Hepatocyte necroptosis has previously been reported in bacterial hepatitis and TNF challenge (Koschel et al, 2021), ischemia and reperfusion injury (Zhong et al, 2020), chronic alcoholic liver disease (Lu et al, 2016), nonalcoholic fatty liver disease (Afonso et al, 2015;Wu & Nagy, 2020) and from hepatic O-GlcNAc transferase deficiency in mice (Zhang et al, 2019). Similar to hepatocytes, liver macrophages in old mice also expressed necroptosis markers.…”
Section: Discussionmentioning
confidence: 83%
“…The ubiquitylation and deubiquitylation of RIP1/RIP3 regulate the NF-κB activation, apoptotic, and necroptotic pathways 52 , and DUBs such as CYLD 53 , A20 54 , and OTUB1 55 are involved in the regulation of the K63 ubiquitylation of RIP1/RIP3. In this study, we showed that the genetic deficiency of OTUD1 accelerated the TNF-α-induced apoptotic and necroptotic cell death pathways, and the basal K63 ubiquitylation of RIP3 was enhanced in Otud1 -/--MEFs (Figs.…”
Section: Discussionmentioning
confidence: 99%